Chemical Vapor Deposition Strategy of Fe‐N‐C Nanotubes for the Oxygen Evolution Reaction - Xin Liu; Tao Wei; Jonas Englhard; Maïssa Barr; Andreas Hirsch; Julien Bachmann (Advanced Science)
Abstract The conversion of metal‐nitrogen‐carbon (M‐N‐C) nanoparticles derived from conventional metal‐organic frameworks (MOFs) into self‐supporting and well‐defined metal‐nitrogen‐carbon (M‐N‐C) superstructures is essential for various functional applications but remains a significant challenge. In this study, a versatile chemical vapor deposition (CVD) strategy is developed for solvent‐free synthesis of self‐supporting carbonaceous nanotubes doped with metal and nitrogen (MNCT). The stable carbonaceous nanotubes doped with Fe and N (FeNCT) fabricated here exhibit excellent electrocatalytic performances for the oxygen evolution reaction (OER) and outperform the carbonaceous film doped with Fe and N grown on carbon foil directly (FeNC/CF), which demonstrates the advantages of the superstructure of FeNCT. This strategy also provides a way to tailor the metal‐nitrogen‐carbon nanotubes (MNCT) catalyst according to the feature of the reactor and exhibits many advantages, such as wide applicability and facile scalability.